Research on the regulation of gut microbiota homeostasis and immune function in asthmatic mice by Huanglong Zhixiao Formula - Chen, Yong-xia; Xuan, Yin-shuang; Wang, Ming-hang; Li, Ya; Shi, Sheng-ming; Zhao, Hao-yu; Niu, Yi-hao; Chen, Min; Li, Su-yun (Frontiers in Microbiology, 2026)
BackgroundAsthma affects approximately 334 million people worldwide. Accumulating evidence indicates that gut dysbiosis exacerbates airway inflammation through the gut–lung axis. In the present study, using an OVA-induced murine model of asthma, we investigated whether Huanglong Zhixiao Formula (HLZXF) restores gut lung homeostasis by reshaping the gut microbiota and enhancing intestinal barrier function, thereby attenuating pulmonary pathological changes.MethodsFemale BALB/c mice were randomly assigned to three groups (n = 15 per group): Control (C), Asthma Model (MX), and HLZXF-treated (ZG) groups. Asthma was induced by OVA sensitization and challenge over a 6-week period. The ZG group received daily oral gavage of HLZXF, 1 h prior to each OVA challenge. Fecal samples were collected for metagenomic sequencing. Lung and intestinal tissues were excised for HE and IHC staining of tight junction proteins, including Claudin, Occludin, and ZO-1. Alpha and beta diversity analyses were conducted to evaluate the composition and structure of the gut microbiota.ResultsWe analyzed the structure of the gut microbiota, detected the expression levels of intestinal barrier-related proteins, and assessed inflammatory injury in the lungs and intestines. Results demonstrated that HLZXF significantly ameliorated gut microbiota dysbiosis in asthmatic mice, as evidenced by the significant enrichment of Heminiphilus faecis and Paramuribaculum intestinale. Additionally, certain fungal taxa, such as Piromyces finnis and Rhizopus arrhizus, were significantly enriched in the ZG group. HLZXF also significantly upregulated the expression levels of the tight junction proteins Claudin, Occludin, and ZO-1 in intestinal tissues, thereby promoting the repair of the intestinal mucosal barrier. Furthermore, HLZXF significantly attenuated inflammatory cell infiltration and tissue injury in the lungs and intestines, alleviated alveolar septal thickening, and enhanced the integrity of the intestinal mucosal barrier.ConclusionThis study elucidates the potential therapeutic mechanisms of HLZXF in the treatment of asthma from the perspective of gut microbiota and intestinal barrier function. It highlights that HLZXF can attenuate pulmonary inflammation by regulating the balance of gut microbiota and enhancing intestinal barrier function.